Selective effects of phorbol 12-myristate 13-acetate on myofibrils and 10-nm filaments. - Croop, J (1980)
Phorbol 12-myristate 13-acetate (PMA) has a prompt and selective catabolic effect on striated myofibrils in postmitotic myotubes. Fluorescein-labeled antibodies against light meromyosin were used to follow the effects of PMA on the muscle-specific myosin in myofibrils. The response of actin filaments was monitored by decoration with heavy meromyosin. The response of the two types of 10-nm filaments in myotubes was followed by fluorescein- and rhodamine-labeled antibodies to the fibroblastic and muscle-specific filament proteins, respectively. Within 2-3 days, PMA induced dismantling of virtually every striated myofibril in every myotube in the culture. These myotubes bound little or no anti-light meromyosin, and tests to detect the alpha-actin filaments of the myofibrils with heavy meromyosin were negative. In contrast, the nonmuscle actin in the subsarcolemmal microfilaments persisted in PMA-treated myotubes and was decorated with heavy meromyosin. The sarcoplasmic reticulum, mitochondria, and Golgi bodies appeared normal. Myotubes depleted of myofibrils by PMA displayed large numbers of muscle-specific 10-nm filaments. This preferential degradation of the myosin and actin of the myofibrils were reversible. These myotubes formed a normal complement of myofibrils 24-48 hr after removal of PMA. When, after 3 days in PMA, the cultures were treated for an additional 3-8 days, a transitory subpopulation of PMA-resistant myotubes appeared.